SYSTEMATIZATION OF CONSTRUCTIVE-COMPOSITION SOLUTIONS IN THE DESIGN OF THE NECK OF MILITARY CLOTHING - OSTAPENKO, Nataliia; RUBANKA, Alla; OLIINYK, Halyna; LUTSKER, Tetayna; VARVOLIK, Victoriia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article analyzes and summarizes the range of modern military clothing of the leading global and domestic manufacturing companies. The most widespread types of structural and compositional solutions for the design of the neck of military clothing are systematized in order to create an information base for further research. Information-research and visual-analytical approaches are applied in combination with general scientific methods of typological systematization and comparative analysis of existing varieties of sewing accessories for the manufacture of military clothing of foreign and domestic production. The structural and compositional solutions for the design of the neck, such as the collar and hood, are systematized according to various features, their types are characterized, and the characteristic structural and compositional solutions are described in terms of shape, degree of fit, method of connection, etc. An information base has been developed and the types of collars and hoods of military clothing are graphically presented. On the basis of the obtained results, recommendations are formulated regarding the prospective direction of improving the design of a rational structure with the introduction of progressive technology for the manufacture of military clothing. The practical significance of the obtained results lies in the identification of the main varieties of the existing neck design solutions. The results can be used in the further development of the specified clothing.